The Effects of Cr and Mo on the Microstructure and Mechanical Properties of As-Cast TiAl Alloys - Husni Usman; Ahmad Fauzi Mohd. Noor; Rizal Astrawinata (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
The effect of the alloying elements of Cr and Mo on the microstructure and mechanical properties of as-cast TiAl alloys produced by a locally made arc-melting furnace was studied. X-ray diffraction (XRD) was used to identify the phases present in the samples. The microstructure of the TiAl samples was characterized using scanning electron microscopy combined with energy dispersive spectroscopy (EDS). Compression tests were carried out at room temperature using an Instron servohydraulic testing machine. The results show that the Ti-48Al alloy exhibited a duplex microstructure, whereas with the addition of Cr a nearly lamellar microstructure was observed in Ti-48Al-2Cr and with the addition of both Cr and Mo also in Ti-48Al-2Cr-2Mo. The hardness values increased slightly as compared to the Ti-48Al alloy with the addition of the alloying elements. The presence of Cr in Ti-48Al-2Cr resulted in a slight increase in compressive fracture strain. The as-cast Ti-48Al-2Cr-2Mo alloy produced a higher yield strength and fracture strain in compression as compared to the other as-cast TiAl alloys. On the fracture surfaces of the as-cast TiAl alloys, mixed brittle transgranular and interlamellar fracture modes were predominantly observed.